2021
DOI: 10.1002/nop2.1130
|View full text |Cite
|
Sign up to set email alerts
|

Ambivalent heroism? – Psychological burden and suicidal ideation among nurses during the Covid‐19 pandemic

Abstract: Aim During the Covid‐19 pandemic, the risk for nurses’ mental health has rapidly increased. The two main goals of this study were the examination of (1) the psychological burden and (2) of suicidal ideation and its associated risk factors one year after the Covid‐19 pandemic begun. Design This was a cross‐sectional online survey. Methods N = 1311 nurses (96.9% female) aged 18–63 years (M = 30.96, SD = 8.48) were assessed for various symptoms of psychological burden, suicidal ideation and behaviour and its risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 71 publications
1
7
0
2
Order By: Relevance
“…), decreased job performance and job satisfaction, and decreased patient safety (Sung et al, 2021). Höller and Forkmann (2022) found that 52.7% of nurses surveyed during the pandemic reported a medium to high risk for burnout. Sung et al (2021) found the incidence of burnout in surveyed HCWs in Taiwan was 40.3%.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…), decreased job performance and job satisfaction, and decreased patient safety (Sung et al, 2021). Höller and Forkmann (2022) found that 52.7% of nurses surveyed during the pandemic reported a medium to high risk for burnout. Sung et al (2021) found the incidence of burnout in surveyed HCWs in Taiwan was 40.3%.…”
Section: Resultsmentioning
confidence: 99%
“…Ariapooran and Amirimanesh (2020) found that 15.38% of the nurses surveyed who were working in Iranian hospitals reported moderate to severe depression, 27.56% had plans for suicide and 9.94% had active suicidal desire. Höller and Forkmann (2022) found that one‐fifth of the nurses they studied during the pandemic reported suicidal ideation in the past 4 weeks and almost half reported lifetime suicidal ideation. Depression, agitation, perceived burdensomeness and previous suicide attempt(s) were associated with suicidal ideation (Höller & Forkmann, 2022).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations